Peranan Corporate Social Responsibility Terhadap Penghindaran Pajak Pada Bank Konvensional - Meirina, Elsa; Hermanto, Yondra (Yayasan Rahmatan Fidunya Wal Akhirah, 2022)
The purpose of the research the author did was to determine the effect of CSR on the tax evasion. Objects in this study on conventional banks. The amount of data in this study is as much as 5 years 2016-2020. The Data in this research is sourced from secondary data obtained from the annual report, the financial statements of the conventional banks. Based on the results of the study, the variable observed. It can be concluded that CSR negatively affect the tax avaasion. Further research should increase the sample and the addition of the period to develop the research. And discuss the complete aspects of CSR, to further develop the indicators in addition to used in this study.